ANALISIS TERHADAP HADIS-HADIS PEMBERDAYAAN PEREMPUAN - Nofry Andi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2018)
In 2000 with the issuance of Presidential Instruction No. 9 concerning Gender Mainstreaming in National Development with the aim of accelerating national development in various fields of life in accordance with the mandate of opening the 1945 Constitution. This Instruction instructs all Ministries / Institutions and Governments both central and regional to mainstream gender in the entire development process from planning to evaluation. The campaign for gender mainstreaming in development is a strategy to reduce the gap between Indonesian male and female residents in accessing and obtaining development benefits and increasing their participation in decision making and control over development resources.